2014
DOI: 10.1002/ijc.28835
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to secondhand tobacco smoke and lung cancer by histological type: A pooled analysis of the International Lung Cancer Consortium (ILCCO)

Abstract: While the association between exposure to secondhand smoke and lung cancer risk is well established, few studies with sufficient power have examined the association by histological type. In this study, we evaluated the secondhand smoke-lung cancer relationship by histological type based on pooled data from 18 case-control studies in the International Lung Cancer Consortium (ILCCO), including 2,504 cases and 7,276 controls who were never smokers and 10,184 cases and 7,176 controls who were ever smokers. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 41 publications
4
94
1
6
Order By: Relevance
“…There are also indications that second-hand smoking (passive smoking) also contributes to the development of the disease (13,14). Passive smoking has been blamed for the 1.6% of total cases of LC (1).…”
Section: Risk Factorsmentioning
confidence: 99%
“…There are also indications that second-hand smoking (passive smoking) also contributes to the development of the disease (13,14). Passive smoking has been blamed for the 1.6% of total cases of LC (1).…”
Section: Risk Factorsmentioning
confidence: 99%
“…İESD maruziyeti ile alınan karsinojen dozları aktif sigara kullanımı ile alınandan çok daha düşük olsa da, İESD maruziyeti çocukluk çağında başlayıp tüm ömre yayılabilir (97,98) . Yapılan bir çalışmada, İESD maruziyetinin dünya çapında akciğer kanserine bağlı 21,400 ölümden sorumlu olduğu tahmin edilmiştir (25) .…”
Section: İki̇nci̇ El Si̇gara Dumaninin Eri̇şki̇nlerde Sağlik üZeri̇ndeki̇ Sounclassified
“…Yapılan bir çalışmada, İESD maruziyetinin dünya çapında akciğer kanserine bağlı 21,400 ölümden sorumlu olduğu tahmin edilmiştir (25) . Toplam 18 vaka-kontrollü çalışmanın 2014 yılında yapılan analizinde ise hiç sigara içmemiş kişiler arasında İESD'ye maruz kalanların akciğer kanseri açısından risk oranlarının 1.31 olduğu tespit edilmiştir (97) . Sigara içmeyenlerde görülen akciğer kanserlerinin nedeni tahminen olguların %17'sinin çocukluk ve adolesanlık döneminde yüksek düzeyde İESD'ye maruz kalmaları-na bağlı olabilir (99) .…”
Section: İki̇nci̇ El Si̇gara Dumaninin Eri̇şki̇nlerde Sağlik üZeri̇ndeki̇ Sounclassified
See 1 more Smart Citation
“…Thus, primary prevention of lung cancer is serious. Many studies have shown that lung cancer is associated with genetic factors [15,16] and environmental factors including tobacco use [17], alcohol consumption [18], and intake of fruit, vegetables [19], and vitamins [20,21] can also affect the incidence of lung cancer. The work influence that dietary factors may have upon the occurrence of this neoplasm and on the causes of possible effect [22].…”
Section: Introductionmentioning
confidence: 99%